Characterization of 9 polymorphic microsatellite loci in Lamellibrachia sp 2, a tubeworm found at deep-sea hydrothermal vents and cold seeps - Jacobson, A; Plouviez, S; Thaler, A D; Van Dover, C L (Conservation Genetics Resources, 2013)
Lamellibrachia sp. 2 is a deep-sea vestimentiferan tubeworm found at hydrothermal vents on the Mid-Cayman Spreading Center and at hydrocarbon seeps in the Gulf of Mexico and off the coast of Barbados. Nine selectively neutral and unlinked polymorphic microsatellite loci were developed for this species. Eight of these loci conformed to Hardy-Weinberg expectations. Average observed heterozygosity ranged from 0.14 to 0.92. Microsatellites developed for Lamellibrachia sp. 2 are being deployed to study connectivity and gene flow among populations of this species.
Keywords: ROV Jason (Remotely Operated Vehicle)